REALLY EXISTING DEMOCRACIES: DEMOCRACY IN A RUSSIAN MIRROR - A. Przeworski (Сравнительная политика, 2015)
Abstract: Leading Western and Russian political scientists contributed to this collective study, which covers issues related to the Russian record of democratic rule and operation of the current political regime in the country, as well as comparative analysis of various concepts of democracy and institutional analysis of various organisations and mechanisms of democratic politics. Moreover it examines major incentives and obstacles to consolidation of democracy.